Seismic behavior of a precast RC frame–shear wall structure using full/half grout sleeve connections - Wei, Wang; Junwei, Ma; Xingxing, Wang (Engineering structures, 2023)
•The seismic failure behavior of a precast RC frame-shear wall structure using full/half grout sleeve connections is reported.•The different seismic performances of the precast RC frame-shear wall structure and cast-in-situ RC frame-shear wall structure are explored.•The seismic behavior of the precast RC frame-shear-wall structure is analyzed by simulation. To investigate the seismic behavior of precast RC frame–shear wall structures using full/half grout sleeve connections, two RC frame–shear wall structure specimens were constructed and tested under cyclic loadings: the first specimen was a precast RC frame–shear wall structure (Specimen PCFW), and the second specimen was a conventional RC frame–shear wall structure (Specimen RCFW) cast in situ. The seismic performance of Specimens PCFW and RCFW including the failure modes, hysteretic responses, and energy dissipation capacities was investigated. Furthermore, the mechanical behavior of Specimen PCFW was numerically simulated using the OpenSees software. The test results show that the crack distribution of Specimen PCFW is more dispersed than that of Specimen RCFW. In particular, few cracks appear in the area of full/half grout sleeves in Specimen PCFW. However, the damage to the concrete around the half grout sleeves of the side columns in the shear wall of Specimen PCFW in the 1st story was more severe than that in the corresponding region of Specimen RCFW for a less thick concrete cover. Compared to Specimen RCFW, Specimen PCFW exhibits higher lateral bearing capacity, better energy dissipation ability, and slightly lower ductility. In addition, assuming the equivalent principle of rebar area, the mechanical behavior of Specimen PCFW can be effectively simulated using the nonlinear multilayer shell element in the OpenSees software.